Group decision making through nominal group technique: an empirical study - Islam, Rafikul (Inderscience, 2010)
As a decision making tool in a group setting, the nominal group technique (NGT) has been widely applied by policy makers in numerous organisations. Many researchers have also conducted experimental studies on NGT to explore its various features that make the technique distinguishable from other related techniques including traditional interactive group and Delphi techniques. The purpose of the present research is to empirically investigate the outputs generated from various uniform nominal group sessions on a common issue. Conducting eight nominal group sessions that consist of 244 undergraduate students in Business Administration, Accounting and Engineering across several academic sessions, we find that most of the important inputs on the issue appear in every list of top ten inputs obtained from the sessions. The implication of this finding is that, once the outcomes of a nominal group session are known, should there a need arise in future for a different nominal group session but the issue is the same, if the session is conducted, major outcomes of this session will be the same as the previously conducted nominal group session. Therefore, the results of this research are expected to save a considerable amount of time in making decisions using nominal groups.